Alcohol consumption and protective behavioural strategy use among Australian young adults. Issue 1 (2nd January 2016) - Crawford-Williams, Fiona M.; Roberts, Rachel M.; Watts, David
Abstract : This study examines the use of safeguards or protective behaviours by young adults to reduce the harm and negative consequences associated with excessive alcohol consumption. Participants were 210 Australian university students. Participants completed an online questionnaire which focused on their alcohol consumption and engagement in protective behaviours. Results indicate that all participants who consumed alcohol engaged in protective behaviours at some level, with females reporting similar levels of these behaviours to males. Protective strategy use was related to less negative consequences of alcohol use. These findings suggest that the promotion of harm reduction strategies is needed to complement prevention programmes which aim to reduce the consumption of alcohol.